The effect of pineapple cultivation on factors influencing soil erodibility in the Eastern Cape, South Africa - Boucher, Kim Gillian (Rhodes University, Faculty of Science, Department of Geography, 1992)
The study examines the effect of ridged pineapple cultivation on factors influencing the soil erodibility of Glenrosa and Oakleaf soil forms in the Bathurst district of South Africa. A number of physical and chemical variables influencing soil erodibility are investigated, namely soil moisture, bulk density, porosity, infiltration rate, aggregate stability, shear strength, soil texture, soil structure, penetrability, organic carbon, pH and cation exchange capacity. These soil characteristics are examined in undisturbed soils under natural vegetation and compared to those on adjacent traffic areas, pineapple ridges and pineapple furrows. The results of the analyses between the four sample sites indicate that ridged cultivation of pineapples has a negative effect on factors influencing soil erodibility on the areas studied. The results of the analysis within each of the sample sites do not illustrate any clear relationships and thus depict the complexity and multiplicity of the soil erodibility phenomenon. A further study, augmenting the soil erodibility data with actual soil loss data, is recommended
Keywords: Soil erosion -- South Africa; Pineapple industry -- South Africa -- Eastern Cape; Agriculture -- South Africa -- Eastern Cape